The Reading Perception Of Medical Staff About The Use Of Prehospital Ultrasound - Sajid, Muhammad Khalid Mehmood; Alsulaiteen, Hajar; Alsaleh, Mohammed Abdullaziz; Almulhim, Fares Saleh; Alabdulathim, Mohammed Ahmed; Alzaid, Abdulrahman Abdulaziz; Alanazi, Abdulaziz Mohammed; Albutayh, Abdullah Abdulaziz E.; Almulhim, Omar; Alabba, Rabab Hussain (Open Access Publishing Group, 2020)
This study was a focus on the use of pre-hospital ultrasound in Saudi Arabia. Generally, ultrasound is used in a high frequency by health care providers in different countries within hospitals or pre-hospital. The main point of using the ultrasound was to reduce the time of diagnosis at the hospital and decrease the rate of mortality and morbidity. The study was a cross-sectional study and was used to assess the perception of medical staff about the use of pre-hospital ultrasound. This survey study had 130 participants, and 80 of them were agreed to involve in this study. It was conducted in King Abdulaziz Hospital of National Guards, Al Ahsa and College of Applied Medical Sciences, King Saud Bin Abdul Aziz University for Health Sciences, Al Ahsa Campus, Saudi Arabia. ATLAST ti 8 was used for systematic literature review and SPSS v23 obviously for data analysis. This was a new and novel study as the Pre-hospital ultrasound was not used before in the pre-hospital. On the other hand, the findings showed that the participants displayed a high level of interest in improving their knowledge and skills of using ultrasound during its application in the pre-hospital setting. It was also recommended to have more research in future on the subject.